Striking variation in chromosome structure within Musa acuminata subspecies, diploid cultivars, and F1 diploid hybrids - Beránková, Denisa; Čížková, Jana; Majzlíková, Gabriela; Doležalová, Alžběta; Mduma, Hassan; Brown, Allan; Swennen, Rony; Hřibová, Eva (Frontiers in Plant Science, 2024)
The majority of cultivated bananas originated from inter-and intra (sub)specific crosses between two wild diploid species, Musa acuminata and Musa balbisiana. Hybridization and polyploidization events during the evolution of bananas led to the formation of clonally propagated cultivars characterized by a high level of genome heterozygosity and reduced fertility. The combination of low fertility of edible clones and differences in the chromosome structure among M. acuminata subspecies greatly hampers the breeding of improved banana cultivars. Using comparative oligo painting we investigated large chromosomal rearrangements in a set of wild M. acuminata subspecies and cultivars that originated by natural and human-made crosses. Additionally, we analyzed chromosome structure of F1 progeny that resulted from crosses between Mchare bananas and the wild M. acuminata 'Calcutta 4' genotype. Analysis of chromosome structure within M. acuminata revealed the presence of a large number of chromosomal rearrangements showing a correlation with banana speciation. Chromosome painting of F1 hybrids was complemented by Illumina resequencing, which enabled to identify the contribution of parental subgenomes to the diploid hybrid clones. Balanced presence of both parental genomes was revealed in all F1 hybrids with the exception of one clone, which contained only Mchare specific SNPs, and thus most probably originated from an unreduced diploid gamete of Mchare.